Increasing the Level of Creative Activity of University Students within Framework of Project and Educational Activity - O. L. Rakovskaya (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The actual problem of development of creative abilities of students in the context of project and educational activity is considered. It is emphasized that the solution of the problem is reflected in the current legislation of the Russian Federation in the field of education. From the authors’ point of view, educational project is a didactic tool, student activities of cognitive, creative or game character, carrying out at a collective level and involving a common goal and a coordinated methodology. Based on the works of modern researchers, the levels of disclosure of creative abilities of students are determined, representing the degree of independence, mobility, adaptive resources of intelligence and other individual properties essential for the full development of the student. It is noted that the most productive vector of work for the disclosure of students’ creative potential is the formation of a system of psychological and pedagogical factors that allow the student to take a firm individual position in overcoming the difficulties that occur in the context of design activities, and solve them in a creative way. Based on the study, the authors argue that the conditions have a positive impact on the improvement of mental, social, creative potential of the individual, lead to improved self-esteem, student’s understanding of independence, not only in the framework of design and educational activities, but also in future profession.